Surgical Procedure Simulation via Three Dimensional Computer Aided Reconstruction of Dysplastic Canine Hips - Riley, S. M.; Miller, C. W.; Dobson, H.; Binnington, A. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
The purpose of this study was to evaluate the use of three dimensional imaging techniques in veterinary orthopaedic surgery to measure hip congruity and predict changes in congruity resulting from triple pelvic osteotomies of canine hips. Preoperative, postoperative, and post-simulation measurements of congruity were obtained from eight canine hips by determination of Norberg angles from ventrodorsal pelvic radiographs (1), and lateral centre-edge (CE) angles from three dimensional (3 D) reconstructions of computed tomography (CT) scan data (2). Half of the hips were treated with a triple pelvic osteotomy with 30 degrees of axial rotation, and the other half served as approached but unoperated controls. Each measurement was performed three times by a single evaluator blinded to the identity of each hip. Lateral centre-edge angle measurements were more precise than Norberg angle measurements as determined by the calculated measurement of reliability (R = 0.78 and 0.68 respectively). Triple pelvic osteotomy resulted in an increase in congruity (as measured by lateral CE angles) of 52.2 ± 4.6 degrees compared to -3.0 ± 6.3 degrees in the control hips. The medical imaging programme used to perform the 3D reconstructions from CT scan data also allowed manipulation of the resulting preoperative 3D images to simulate on the computer screen the triple pelvic osteotomies performed on the gross specimens. Surgical procedure simulation predicted the change in congruity (as measured by lateral CE angles) of operated hips to be 43.5 ± 8.8 degrees. The images obtained by 3D reconstruction were very sensitive indicators of gross hip morphology. Visualization of structures, superimposed or surrounded by bone, was easily performed on the computer by interactive manipulation of the three dimensional CT scan reconstructions. In addition to its unique imaging capabilities, this technique appears to be a useful method for non-invasive measurement and prediction of the effects of triple pelvic osteotomy on hip congruity in dogs.Three dimensional (3D) computer aided image reconstructions were performed on tomographic scan data collected from dysplastic canine pelves before and after triple pelvic osteotomy (TPO). Descriptions of imaging capabilities and the application of lateral centre-edge angles for the determination of hip congruity are reported. Simulations performed on the computer accurately predicted the changes in congruity achieved by surgery.
Keywords: Three dimensional image reconstruction; triple pelvic osteotomy; surgical simulation; coxofemoral joint congruity; centre-edge angle